2012
DOI: 10.4085/1062-6050-47.5.08
|View full text |Cite
|
Sign up to set email alerts
|

National Athletic Trainers' Association Position Statement: Anabolic-Androgenic Steroids

Abstract: Abusers of AAS often rely on questionable information sources. Sports medicine professionals can therefore serve an important role by providing accurate, reliable information. The recommendations provide health care professionals with a current and accurate synopsis of the AAS-related research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 137 publications
(870 reference statements)
3
48
0
8
Order By: Relevance
“…The high use of supratherapeutic doses of AAS by bodybuilding participants to improve body composition is well known [14,15]. The amounts of AAS used by the participants in this present study are similar to those previously reported [2,3], and are many times greater than endogenous testosterone production, which is around 2.5-11 mg/day for men and 0.25 mg/day for women [16].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The high use of supratherapeutic doses of AAS by bodybuilding participants to improve body composition is well known [14,15]. The amounts of AAS used by the participants in this present study are similar to those previously reported [2,3], and are many times greater than endogenous testosterone production, which is around 2.5-11 mg/day for men and 0.25 mg/day for women [16].…”
Section: Discussionsupporting
confidence: 79%
“…The amounts of AAS used by the participants in this present study are similar to those previously reported [2,3], and are many times greater than endogenous testosterone production, which is around 2.5-11 mg/day for men and 0.25 mg/day for women [16]. Long-term abuse of AAS is associated with cardiomyopathy and atherosclerotic vascular disease caused by detrimental lipid changes [15,17]. A recent retrospective study reinforced the association between long-term abuse of AAS and premature cardiovascular disease (CVD) [7].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Dando maior enfoque a testosterona que é o principal andrógeno promotor de características masculinas, além da manutenção do balanço de nitrogênio e facilitador de síntese proteica 12 , a testosterona possui efeitos em diferentes tecidos, ocorrendo posteriormente à metabolização da testosterona podendo originar outros esteroides ativos, dentre eles: a dihidrotestosterona (DHT) e o estradiol, e seus efeitos parecem estar ligados à própria testosterona 12 . Segundo Fortunato 22 , a testosterona e a DHT tem o mesmo receptor de ação, o receptor de androgênio, contudo a substância que tem mais afinidade para ativação da expressão gênica sendo mais eficiente é o composto DHT.…”
Section: Utilização Dos Esteroides Anabolizantes Em Idosos Sarcopênicosunclassified
“…Paradoxalmente à perda muscular, temos os esteroides anabolizantes androgênicos (EAA), uma classe terapêutica sintética, análogos da testosterona. Apresentam efeitos anabólicos -estímulo à síntese proteica e androgênicos -características masculinizantes 12,13 . A utilização de esteroides para aumentar a massa muscular iniciou-se ao redor de 1940 tanto em animais de corte como em fisiculturistas.…”
Section: Introductionunclassified